(untitled) (The Research of Medical Science Review, 2024)
This study investigates the effectiveness of mindfulness-based interventions (MBIs) in reducing symptoms of attention-deficit hyperactivity disorder (ADHD) in children. A randomized controlled trial design was employed, with 140 children aged 8–12 years diagnosed with ADHD, and one of their parents, from Karachi, Pakistan. The intervention group participated in eight weekly 90-minute mindfulness sessions, while the control group received no intervention. Outcomes were measured at baseline (T0), post-intervention (T1), and at three (T2) and six (T3) months follow-up, focusing on ADHD symptoms, attention, mindfulness levels, parental stress, and positive parenting practices. Results indicated that the intervention group showed significant improvements in ADHD symptoms, attention, mindfulness, and parental stress compared to the control group. These effects were sustained at follow-up assessments, although some outcomes showed a slight reduction over time. The findings suggest that MBIs can be an effective and long-term intervention for improving ADHD symptoms in adolescents and reducing stress for their parents.